2012
DOI: 10.1016/j.bbmt.2011.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Cytogenetics in Patients with Acute Myelogenous Leukemia in Complete Remission Undergoing Allogeneic Transplantation: A Center for International Blood and Marrow Transplant Research Study

Abstract: Cytogenetics play a major role in determining the prognosis of patients with AML. However, the existing cytogenetics classifications were developed on chemotherapy-treated patients and may not be optimal for patients undergoing allogeneic hematopoietic cell transplantation (HCT). We studied 821 adult patients reported to the CIBMTR who underwent HCT for AML in first or second CR between 1999 and 2004. We compared the ability of the 6 existing classifications to stratify patients by overall survival (OS). We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 22 publications
4
62
0
Order By: Relevance
“…We have addressed the latter issue by incorporating the year of transplant into the multivariable analysis, and this did not demonstrate any influence on the prognostic value of the developed scoring system. We must also note that in the present study, cytogenetic risk was classified according to the CIBMTR criteria, 11 which have not been confirmed in an independent validation. Repeat analysis of a larger, independent multicenter data set using the score we have developed would be required in validating the prognostic value of the score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have addressed the latter issue by incorporating the year of transplant into the multivariable analysis, and this did not demonstrate any influence on the prognostic value of the developed scoring system. We must also note that in the present study, cytogenetic risk was classified according to the CIBMTR criteria, 11 which have not been confirmed in an independent validation. Repeat analysis of a larger, independent multicenter data set using the score we have developed would be required in validating the prognostic value of the score.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning intensity was myeloablative in 261 patients (67%) and reduced-intensity in 126 patients (33%). Concerning cytogenetic risk according to the CIBMTR criteria, 11 13 patients (3%) presented with favorable, 278 patients (72%) with intermediate and 34 patients (9%) with unfavorable risk cytogenetics. Among the intermediate cytogenetic risk patients, 154 demonstrated normal karyotype; however, a minority had data available on mutational status (FLT3-ITD and NPM1 mutations).…”
Section: Patient and Transplant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictive role of cytogenetic risk for patients receiving an allograft as salvage therapy remains under debate. Studies by Armand et al, Fung et al, and Ferrant et al, [23][24][25] reported an increased RR and worse OS for patients transplanted with unfavorable cytogenetics. Our study demonstrated similar outcomes for patients transplanted in CR2 independent of their cytogenetic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant of patients with AML in first CR: in patients who achieved CR, the role of allo-SCT is still under discussion. A variety of clinical studies have tried to evaluate the benefit of transplant in this situation, but most studies were non-randomized, non-controlled trials 3,5,6 . Only a few trials that were analyzed based on donor availability ('genetic' or 'biological' assignment) were useful as supporting evidence in the guideline recommendations, which were mainly based on cytogenetic risk factors.…”
Section: Allogeneic Stem Cell Transplant (Allo-sct)mentioning
confidence: 99%